Brewer's spent grain : a valuable feedstock for industrial applications - Mussatto, Solange I. (2014)
Brewer's spent grain (BSG) is the most abundant by-product generated from the beer-brewing process, representing approximately 85% of the total by-products obtained. This material is basically constituted by the barley grain husks obtained as solid residue after the wort production. Since BSG is rich in sugars and proteins, the main and quickest alternative for elimination of this industrial by-product has been as animal feed. However, BSG is a raw material of interest for application in different areas because of its low cost, large availability throughout the year and valuable chemical composition. In the last decade, many efforts have been directed towards the reuse of BSG, taking into account the incentive that has been given to recycle the wastes and by-products generated by industrial activities. Currently, many interesting and advantageous methods for application of BSG in foods, in energy production and in chemical and biotechnological processes have been reported. The present study presents and discusses the most recent perspectives for BSG application in such areas. © 2013 Society of Chemical Industry.